Exploring University Students' Library Engagement: Reading Habits, Preferences, and Gender Dynamics - Adetayo, Adebowale; Alawiye, Mariam Kehinde; Emmanuel, Sunday Oluwafemi; Omotoso, Akinkunmi Oluesun; Bello, Taoffik Olatunde (MO.RI Publishing, 2024)
This cross-sectional study aimed to investigate university students' library engagement, emphasizing preferences, motivations, and reading habits, with an additional focus on gender dynamics. A total of 373 participants were involved in the research, and data were collected through a self-administered questionnaire. Descriptive statistics were used to analyze the participants' reading habits in different library sections, types of books read, and reasons for their preference for reading in the library. The Kruskal-Wallis test was employed to examine potential gender differences in these variables. The findings revealed variations in the frequency of students' reading activities across different library sections, with the main reading room being the most preferred section. The study also identified specific book types, such as personal notebooks and library textbooks, that were frequently read by students. Reasons for students' preference for reading in the library included the motivating environment, availability of book options, assistance from librarians, and fewer distractions compared to other places. The results of the Kruskal-Wallis test indicated significant gender differences in the ranks for certain library sections, book types, and reasons for reading in the library. These findings provide valuable insights into students' reading habits and preferences, highlighting the importance of creating diverse reading spaces, expanding book collections, promoting a supportive library environment, and enhancing librarian support. The implications of the study underscore the need for gender-inclusive services, thoughtful space design, and comprehensive collection development to meet the evolving needs of students and foster a reading culture in libraries.